The relationship between oxygen extraction in the arms and legs to force and exercise intensity in diagonal skiing - Björklund, G.; Stöggl, T.; Carlsson, L.; Dvoren, L.; Holmberg, H. C. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Diagonal skiing (DIA) is the main classical cross-country technique used when skiing uphill. Two interesting findings when examining this technique at submaximal workloads have been that 1) O2 extraction was lower in the arms than the legs (Calbet et al., 2005) and 2) lactate oxidation mainly occurred in the leg muscles simultaneously with a high lactate production in the arms (Van Hall et al., 2003). At present no data have described how these findings may be associated with force generation and the muscle activity measured by electromyography (EMG). Thus, the aims of this study were to examine i) the interaction between physiological and biomechanical variables and ii) the effect of changes in submaximal exercise intensities in diagonal skiing. Methods: Eleven elite XC skiers (age 22±3yr; VO2max 69±3 mL/kg/min, obtained during DIA on a treadmill) performed a protocol of 3 min at 90% followed by 6 min at 70% of VO2max DIA. Cardiorespiratory data were collected continuously, along with determination of blood gases and metabolites from a. femoralis, v. femoralis and v. subclavia. Pole and foot forces (Pedar, Mobile 100Hz) and EMG data from six lower and upper body muscles (Noraxon, 3000 Hz) were collected. Changes to variables between 90% and 70% of VO2max were analyzed using paired sample t-tests. Pearson correlations were used to evaluate the relationships between variables. á was set to 0.05. Results: The O2 extraction was higher for legs than arms at both exercise intensities (p<0.05). The arms O2 extraction decreased more than that of the legs when intensity decreased (p<0.01). Leg and pole peak forces and muscle activity increased with intensity (p<0.01), whereas the impulses of forces and the ratio between the arm and leg force remained constant. O2 extraction was negatively associated with iEMG activity in % of MVC at both intensities (r=-0.56 to -0.91, p<0.05 to p<0.001). The lactate a-v difference in the arms was associated with the leg impulses at both intensities (r=-0.53 and -0.57, p<0.05) and with a cycle rate at 70 % of VO2max (r=0.77, p<0.01). Discussion: A decreased relative use of the arms and legs` MVC at a given % of VO2max decreases O2 extraction. The difference in O2 extraction between the arms and legs increased at decreased exercise intensities, mainly due to decreased arm O2 extraction despite similar changes in muscle activity. A high leg impulse decreases lactate occurrence in the arms, regardless of exercise intensity, whereas a low cycle rate is important only during medium intensity DIA.